Entre a imagem e o silêncio: representação e recepção em paisagem após a batalha (1970) de Andrzej Wajda - Gois, Rafael Leopoldino França (2021)
This research seeks to discuss Andrzej Wajda's cinema from the perspective of Representation and Reception. Thinking about how the director was guided by the production of historical films, and consequently how he provoked the past in the face of the problematizations of his time. For this, we will think about the relationships that enabled the production of this cinema, using as a documentary basis the bibliography on Polish cinema produced by the State under the regime of the People's Republic of Poland, as well as interviews with the Polish director, and in particular the film Landscape After Batalha (1970) and its troubled reception by denouncing of Polish anti-Semitism. To discuss Wajda's cinema is also to discuss the historical narratives in Poland during the post-war period, and the impact of these narratives both on Polish cultural memory and on the Polish State. Through these analyses, we will be able to contribute to the debate on Polish historiography or even on the historiography of Polish cinema, which is still little explored outside Eastern Europe.